Stične točke pri oblikovanju slovaškega in prekmurskega knjižnega jezika - Jesenšek, Marko (Jezik in slovstvo, 2001)
In the 18th century Hungarian state, two new literary languages emerged (Slovakian and Slovenian Prekmurski) whose normative design was shaped in a similar way. Several of these similarities are discussed in the article. However, the subsequent development of the two languages proceeded along differnet paths: today Slovakian is an independant literary language of one ofthe Slavic nations, while the Prekmurski literary language merged with the central Slovene into so-called new Slovene, i. e. a uniform literary language of all Slovenes.
Keywords: Slovene; slovenščina; Slovene dialects; slovenska narečja; Prekmurian; prekmurščina; slovaščina; standard language; knjižni jezik